The Characteristics of Heavy Ozone Pollution Episodes and Identification of the Primary Driving Factors Using a Generalized Additive Model (GAM) in an Industrial Megacity of Northern China - Liuli Diao; Xiaohui Bi; Wenhui Zhang; Baoshuang Liu; Xuehan Wang; Linxuan Li; Qili Dai; Yufen Zhang; Jianhui Wu; Yinchang Feng (Atmosphere, 2021)
Tropospheric ozone is the only normal pollutant with a continuously increasing annual average concentration worldwide. In this study, data were monitored at the Nankai University Air Quality Research Supersite (NKAQRS) (38.99° N, 117.33° E) between 1 April, and 31 August from 2018 to 2020, 33 O3 episodes from 2018 to 2020 were analyzed to reveal the characteristics of O3, VOCs and OFP during O3 episodes and to evaluate the driving factors. The O3 episodes showed a decreasing trend in terms of pollution frequency, days, heavy pollution duration and peak concentration. Ethane, acetylene, cyclopentane, and methylcyclopentane were the major types in 2020, while 1-hexene was the main component in 2019. The main ozone-contributing species in 2020 were propene cyclopentane methylcyclopentane and ethylene. Alkenes were important contributors to ozone formation. Using generalized additive models (GAMs), the explanatory variables in the study are divided into environmental and meteorological factors, and 16 impact factors are selected as explanatory variables. We found that the influence of these meteorological factors on O3 pollution was nonlinear and impacted by the interaction between variables. O3 episodes were mainly driven by meteorological and precursor (NO) factors in 2018, while meteorological conditions (T), followed by precursor (NO2) were the driving factors in 2019 and 2020, suggesting that O3 episodes were mainly driven by meteorological conditions.